2015
DOI: 10.1007/s12601-015-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Under-ice measurements of suspended particulate matters using ADCP and LISST-Holo

Abstract:  Using a mooring package comprising an acoustic Doppler current profiler (ADCP) and holographic imaging system, a 1-day ice camp study was performed under the Arctic sea ice in the northern Chukchi Plateau to estimate vertical and temporal variations in total suspended particulate matter (SPM). In early August, the SPM in the upper mixed layer (~15 m and above) under sea ice reached up to about 100 mg l -1 even under the offshore regime. Results of both holographic and microscopic analyses showed that dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The reexamination of datasets from previous expeditions over the past two decades suggests that UIBs may have already had a circumpolar distribution. High concentrations of phytoplankton biomass under Arctic sea ice (typically with >50% coverage) have been reported in areas as widespread as Resolute Passage and Allen Bay in the Canadian Arctic Archipelago (Michel et al, 1996;Fortier et al, 2002;Duerksen et al, 2014;Galindo et al, 2014Galindo et al, , 2015Galindo et al, , 2016Mundy et al, 2014), Baffin Bay (Hussherr et al, 2017;Oziel et al, 2019), the Greenland Sea (Mayot et al, 2018), the Barents Sea (Strass and Nöthig, 1996;Assmy et al, 2017;Pavlov et al, 2017;Kauko et al, 2019), the Laptev Sea (Lalande et al, 2014), the Chukchi Sea (Yager et al, 2001;Arrigo et al, 2012Arrigo et al, , 2014Ha et al, 2015;Hill et al, 2018), and the Central Arctic (Laney et al, 2014;Boles et al, 2020). Many locations where UIBs were observed had first year sea ice, which was not the case in the 1980s when multi-year sea-ice was more prevalent (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…The reexamination of datasets from previous expeditions over the past two decades suggests that UIBs may have already had a circumpolar distribution. High concentrations of phytoplankton biomass under Arctic sea ice (typically with >50% coverage) have been reported in areas as widespread as Resolute Passage and Allen Bay in the Canadian Arctic Archipelago (Michel et al, 1996;Fortier et al, 2002;Duerksen et al, 2014;Galindo et al, 2014Galindo et al, , 2015Galindo et al, , 2016Mundy et al, 2014), Baffin Bay (Hussherr et al, 2017;Oziel et al, 2019), the Greenland Sea (Mayot et al, 2018), the Barents Sea (Strass and Nöthig, 1996;Assmy et al, 2017;Pavlov et al, 2017;Kauko et al, 2019), the Laptev Sea (Lalande et al, 2014), the Chukchi Sea (Yager et al, 2001;Arrigo et al, 2012Arrigo et al, , 2014Ha et al, 2015;Hill et al, 2018), and the Central Arctic (Laney et al, 2014;Boles et al, 2020). Many locations where UIBs were observed had first year sea ice, which was not the case in the 1980s when multi-year sea-ice was more prevalent (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…For drifting and transect data collections, central latitude and longitude locations are used. Additional to Table 1, studies that demonstrated indirect evidence of UIBs (e.g., Lalande et al, 2014;Ha et al, 2015;Hussherr et al, 2017) are plotted.…”
Section: Changing Under-ice Light Regime Precursor To Under-ice Bloomentioning
confidence: 99%
“…The LI screening method is optimized for a high-SSC environment where frequent resuspension of cohesive sediments is observed. In offshore areas (e.g., Ha et al, 2015;Many et al, 2019), where the sediment supply is significantly limited, the possibility of hologram contamination caused by the overlapping concentric rings would be considerably low. In this case, the criterion of LI to screen the contamination might be higher than that proposed in this study.…”
Section: Limitationsmentioning
confidence: 99%